Why and how to teach the history of economic thought: Economics as historically produced knowledge - Avi Jonathan Cohen; Ross B. Emmett (Duke University, Center for the History of Political Economy (CHOPE), 2011)
This draft chapter for the Elgar International Handbook on Teaching and Learning Economics is intended to give advice to instructors who might be teaching a history of economic thought course to undergraduates for the first time or who have perhaps been teaching for a while but would like to refresh their courses. We sketch the history of courses in the history of economic thought, the expanding scope and research activity in the field, and offer suggestions and resources for a one-semester course. We suggest learning objectives for organizing the course, and discuss supplementary teaching goals (multidisciplinary scholarship and reading/writing instruction) and teaching challenges (time constraints and selection of readings). Our emphasis is on helping students understand economics - past and present - as historically produced knowledge.
Keywords: A22; A3; B0; B1; B2; B3; B4; 330; history of economic thought; history of economics; teaching; pedagogy; HISRECO; writing instruction; multidisciplinary scholarship